Main trends in the development of automated image processing systems - Konieva, A.; Sotnik, S. V. (ХНУРЕ, 2025)
The paper studies the current trends in the development of automated image processing systems, which play a key role in the digital transformation of various industries. Innovative approaches, such as the integration of artificial intelligence, deep learning and cloud computing, are considered, which can significantly improve the accuracy, speed and scalability of visual data processing. The work emphasizes that the further development of automated image processing systems is an important step for the introduction of innovative solutions in modern technologies. The work allows us to evaluate the importance of such systems for improving the efficiency, accuracy and speed of visual data processing, which is a key factor in progress in the digital age. У роботі досліджено сучасні тенденції розвитку автоматизованих систем обробки зображень, які відіграють ключову роль у цифровій трансформації різних галузей. Розглянуто інноваційні підходи, такі як інтеграція штучного інтелекту, глибокого навчання та хмарних обчислень, що дозволяють значно покращити точність, швидкість та масштабованість обробки візуальних даних. Робота підкреслює, що подальший розвиток автоматизованих систем обробки зображень є важливим кроком для впровадження інноваційних рішень у сучасних технологіях. Робота дозволяє оцінити значення таких систем для підвищення ефективності, точності та швидкості обробки візуальних даних, що є ключовим фактором прогресу у цифрову епоху.
Основні тенденції розвитку автоматизованих систем обробки зображень
Keywords: automated image processing system; artificial intelligence; machine learning; computer vision; система обробки зображень; комп’ютерний зір